Perovskite Solar Cells: Low‐Temperature Fabrication of Efficient Wide‐Bandgap Organolead Trihalide Perovskite Solar Cells (Adv. Energy Mater. 6/2015). Issue 6 (March 2015) - Bi, Cheng; Yuan, Yongbo; Fang, Yanjun; Huang, Jinsong
<x xml:space="preserve">Abstract</x> To match the bandgap of silicon solar cells for tandem devices, Jinsong Huang and co‐workers report the incorporation of Br into perovskite to increase the bandgap to 1.72 eV. In article number 1401616, the efficiency of perovskite solar cell with wide‐bandgap is shown to reach 13.1% with grain size engineering. The wide‐bandgap perovskite solar cells fabricated at low temperature can be directly integrated onto Si for tandem cells, which potentially increases the efficiency to 24.0%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>